2013
DOI: 10.5897/ajbm09.258
|View full text |Cite
|
Sign up to set email alerts
|

Capital adequacy, management and performance in the Nigerian commercial bank (1986 - 2006)

Abstract: This study investigates the impact of bank capital adequacy ratios, management and performance in the Nigerian commercial bank (1986 -2006). The objectives of this paper are: to determine to what extent bank capital adequacy ratios impact on bank performance and also to investigate the extent to which operation expenses has impacted on the return on capital. The study captured their performance indicators and employed cross sectional and time series of bank data obtained from Central Bank of Nigeria (CBN) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…This indicates that a unit increase in capital adequacy ratio will bring about 0.08 unit decrease in ROA. This outcome agrees with the findings of Ikpefan (2013) in Nigeria whose study on the impact of capital adequacy ratios of Nigerian commercial banks from 1986 to 2006 using panel data regression model revealed a negative impact of capital adequacy, measured by shareholders fund over total assets, on return on assets. This result however conflicts with the findings of Ezike and Oke (2013) in Nigeria, Mathuva (2009) in Kenya which gave a positive relationship between CAR and ROA.…”
Section: Results Of the Panel Data Regression Analysissupporting
confidence: 91%
“…This indicates that a unit increase in capital adequacy ratio will bring about 0.08 unit decrease in ROA. This outcome agrees with the findings of Ikpefan (2013) in Nigeria whose study on the impact of capital adequacy ratios of Nigerian commercial banks from 1986 to 2006 using panel data regression model revealed a negative impact of capital adequacy, measured by shareholders fund over total assets, on return on assets. This result however conflicts with the findings of Ezike and Oke (2013) in Nigeria, Mathuva (2009) in Kenya which gave a positive relationship between CAR and ROA.…”
Section: Results Of the Panel Data Regression Analysissupporting
confidence: 91%
“…In other words, Capital adequacy has a significant impact on the bank's performance. Our Results are consistent with the studies of Pastory et al, Frederick, Guisse, Ikpefan, Barnor and Odonkor [74][75][76][77][78]. The Coefficient correlation value shows a negative relationship between Total Deposit to Total Equity ratio and the Bank's performance.…”
Section: Discussionsupporting
confidence: 82%
“…The general capital adequacy proportions of the study demonstrate that Shareholders Fund/Total Assets (SHF/TA) which measures the capital adequacy of banks (danger of default) have significant negative effects on ROA [77].…”
Section: Capital Adequacymentioning
confidence: 99%
“…Secondly, the results from the effect of deposits and loans showed that poor capitalized banks operated with low net worth relative to asset. Ikpefan (2013), "Capital inadequacy has affected the financial health of banks. He explained that an analysis of bank capitalization revealed that as at the end of 1992, almost all banks (120) operating in Nigeria required additional capital totaling N0.6billion to support their volume of trading.…”
Section: Sources Of Capitalmentioning
confidence: 99%
“…Also that loans should be adequately secured to reduce the incidence of non-performing loans to dampen the negative effects of risk management and, thus, enhance capital adequacy of the banks. Ikpefan (2013) investigated the impact of bank capital adequacy ratios, management and performance in the Nigerian commercial bank (1986 -2006). The study captured their performance indicators and employed cross sectional and time series of bank data obtained from Central Bank of Nigeria (CBN) and Annual Report and Financial Statements of the sampled banks.…”
Section: Empirical Reviewmentioning
confidence: 99%